Dynamic reconfiguration of van der Waals gaps within GeTe–Sb2Te3 based superlattices. Issue 25 (16th June 2017) - Momand, Jamo; Wang, Ruining; Boschker, Jos E.; Verheijen, Marcel A.; Calarco, Raffaella; Kooi, Bart J.
Abstract : The van der Waals gaps trapped in GeTe–Sb2 Te3 based superlattices reconfigure themselves throughout the film upon annealing. Abstract : Phase-change materials based on GeSbTe show unique switchable optoelectronic properties and are an important contender for next-generation non-volatile memories. Moreover, they recently received considerable scientific interest, because it is found that a vacancy ordering process is responsible for both an electronic metal–insulator transition and a structural cubic-to-trigonal transition. GeTe–Sb2 Te3 based superlattices, or specifically their interfaces, provide an interesting platform for the study of GeSbTe alloys. In this work such superlattices have been grown with molecular beam epitaxy and they have been characterized extensively with transmission electron microscopy and X-ray diffraction. It is shown that the van der Waals gaps in these superlattices, which result from vacancy ordering, are mobile and reconfigure through the film using bi-layer defects and Ge diffusion upon annealing. Moreover, it is shown that for an average composition that is close to GeSb2 Te4 a large portion of 9-layered van der Waals systems is formed, suggesting that still a substantial amount of random vacancies must be present within the trigonal GeSbTe layers. Overall these results illuminate the structural organization of van der Waals gaps commonly encountered in GeSbTe alloys, which are intimately related to their electronic properties and the metal–insulator transition.